Improved flux pinning properties of Mg exceed MgB2 ceramics with B4C and Dy2O3 additions - Pham, Ha H.; Le, Tien; Pham, An T.; Kang, Won Nam; Nam, Nguyen H.; Anh, Do T.K.; Anh, Nguyen Hoang; Peh, Hoo Keong; Chen, Soo Kien; Man, Nguyen K.; Hong, Vuong Thi Anh; Lee, Hanoh; et al. (Elsevier, 2024)
In this study, MgB2 polycrystals were synthesized via the addition of B4C and Dy2O3. X-ray diffraction confirmed that MgB2 was the predominant phase in all the samples. The superconducting properties of the samples were characterized by in-field temperature-dependent resistivity and magnetization measurements. The upper critical field (Hc2) and the critical current density (Jc) of each sample were estimated. The results indicate significant enhancements in Hc2 and Jc with the optimal addition levels of B4C and Dy2O3. According to collective pinning theory, δl pinning was identified as the dominant pinning type in the fabricated samples. The dominant pinning mechanism was determined to be core surface pinning induced by grain boundaries, which is consistent with predictions made by the Dew–Hughes model.